Editorial: Emergent Effects of Noise in Biology: From Gene Expression to Cell Motility - Diambra, Luis Anibal (2019)
Deterministic modeling coarse-grains unitary events into population behavior, however this approach often misses the diversity of responses in cellular and molecular systems, due to long-time effects of stochastic fluctuations. The origins of stochasticity in biological systems are multiple and it is now generally accepted that this stochasticity can play key roles in emergent biological function at many scales: from intracellular processes to populations of macroscopic individuals. One can distinguish two sources: intrinsic fluctuations related to molecular processes, as those involved in biochemical reactions (in many instances the count of molecules participating in these processes is low, and so their stochastic nature becomes apparent); and extrinsic fluctuations due to random changes in the environment surrounding affecting the time evolution of the system.